2004
DOI: 10.1111/j.1471-4159.2004.02718.x
|View full text |Cite
|
Sign up to set email alerts
|

Nicastrin expression in mouse peripheral tissues is not co‐ordinated with presenilin and is high in muscle

Abstract: Nicastrin was the first binding partner of presenilin (PS) shown to be a critical component of the presenilin/c-secretase complex essential in development and differentiation, and in generation of Alzheimer's disease Ab amyloid peptide. To investigate the function of this glycoprotein, we compared nicastrin and presenilin protein expression in various mouse tissues. Western blot analysis of PS1, PS2 and nicastrin indicates their expression levels are not coordinated. In adult mouse, nicastrin is highly express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 52 publications
(113 reference statements)
0
6
1
Order By: Relevance
“…In silico transcriptome analysis utilizing the GeneSapiens database gave further support to our observation. This finding was unexpected in the light of previous studies showing differential expression of PS1/PS2 and Aph1a/Aph1b among various tissues [11,12,14-16] and the compensatory expression of other members of PS or Aph1 families when the endogenous expression of their counterparts have been artificially suppressed [10,23,29]. However, our results are in line with the studies showing joint expression levels for the various γ-secretase components [12,18,54].…”
Section: Discussioncontrasting
confidence: 61%
“…In silico transcriptome analysis utilizing the GeneSapiens database gave further support to our observation. This finding was unexpected in the light of previous studies showing differential expression of PS1/PS2 and Aph1a/Aph1b among various tissues [11,12,14-16] and the compensatory expression of other members of PS or Aph1 families when the endogenous expression of their counterparts have been artificially suppressed [10,23,29]. However, our results are in line with the studies showing joint expression levels for the various γ-secretase components [12,18,54].…”
Section: Discussioncontrasting
confidence: 61%
“…Some subtle variations have been reported in the cellular distribution profile among the four γ-secretase subunits in selected brain regions as well as in certain peripheral tissues. For example, PEN-2 immunoreactivity, compared to other γ-secretase components, was found to be rather intense in mossy fiber terminal zone of the hippocampus [45], whereas nicastrin, but not PS1, was expressed at relatively high levels in the muscle membranes [21]. Whether these differences reflect unique functions of PEN-2 or nicastrin independent of the γ-secretase remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies showed that components of the γ‐secretase complex are not coordinately expressed in tissues. For example, NCT is highly expressed in muscle cells, whereas PSEN1 is very lowly expressed (Ilaya et al, ). These studies suggested that, in addition to forming the γ‐secretase complex, PSEN1 might also play independent roles in the maintenance of cardiac functions.…”
Section: Discussionmentioning
confidence: 99%